Serum NGAL can act as an early renal safety biomarker during long‐term nucleos(t)ide analogue antiviral therapy in chronic hepatitis B. Issue 10 (11th May 2018) - Carey, I.; Byrne, R.; Childs, K.; Horner, M.; Bruce, M.; Wang, B.; Dusheiko, G.; Agarwal, K.
Summary: Tubular renal toxicity is a side‐effect of long‐term therapy with nucleos(t)ide analogue(s) (NA) in chronic hepatitis B (CHB). There are no established surrogate markers in plasma of early NA‐related toxicity. Neutrophil gelatinase‐associated lipocalin (NGAL) is a protein produced by tubular cells following renal damage. We aimed therefore to retrospectively compare conventional renal markers (estimated glomerular filtration rates (eGFR) and urinary protein/creatinine ratio uPCR) with a sensitive biomarker (NGAL) in CHB patients on long‐term NA therapy and assess the ability of new markers to predict NA‐related renal toxicity (new onset of nonalbumin proteinuria). A total of 192 naïve CHB patients (median age 41 years, 78% males, 25% HBeAg+, 35% cirrhosis) were NA treated for at least 5 years (median 8.34 years, range 5.54‐11.1 years). The eGFR and uPCR were compared at baseline and last clinical visit with serum NGAL concentrations measured by ELISA at same time‐points and assessed according to the presence/absence of nonalbumin proteinuria at last visit. While baseline and last visit eGFR were similar (median:78 vs 84 mL/min), serum NGAL concentrations increased during therapy (median:9.4 vs 16.4 ng/mL, P  < .05). The proportion of patients with proteinuria (uPCR > 15) increased between baseline and last visit (4.6% vs 21.4%, P  < .05), with 30 (16%) patients having de novo nonalbumin proteinuria at last visit. High baseline NGAL concentrations were exclusive to patients with de novo nonalbumin proteinuria (median:31.7 vs 7.8 ng/mL, P  < .01) and baseline NGAL levels >25 mg/mL were predictive of nonalbumin proteinuria at last visit (AUROC = 0.813). In conclusion, serum NGAL can act as a surrogate marker of early renal injury (de novo nonalbumin proteinuria) in CHB on long‐term NA therapy.